Itraconazole Inhibits the Growth of Cutaneous Squamous Cell Carcinoma by Targeting HMGCS1/ACSL4 Axis - Xu, Congcong; Zhuo, Yating; Liu, Yunyao; Chen, Hao (Frontiers in Pharmacology, 2022)
Abstract Background Cutaneous squamous cell carcinoma (cSCC) is a common cutaneous cancer with increasing incidence. Itraconazole has been identified as a potential anticancer drug candidate. However, the role of itraconazole in cSCC was still unclear. Our objective is exploring the therapeutic potential of itraconazole in cSCC and investigate its molecular mechanism. Methods The anti-proliferation effect of itraconazole was tested with CCK-8 assay and clone formation assay. Cell cycle distribution and apoptosis rate were detected using flow cytometry and TUNEL assay, respectively. Transcriptomic and proteomic analyses were used to explore the underlying anti-cancer mechanism. Luciferase reporter assay was used for promoter activity. Reactive oxygen species (ROS), lipid peroxidation and iron accumulation were examined. The in vivo efficacy of itraconazole was assessed in a xenograft model. Results Itraconazole inhibited the cell proliferation, induced apoptosis and blocked cell cycle of cSCC cells. An integrated analysis of transcriptomic and proteomic analyses identified that 3-hydroxy-3-methylglutaryl-CoA synthase 1 (HMGCS1) and acyl-CoA synthetase long-chain family member 4 (ACSL4) were significantly upregulated in A431 cells treated with itraconazole. HMGCS1 silencing reversed the antiproliferative activity of itraconazole in A431 cells. Dual-luciferase assay showed that itraconazole could promote HMGCS1 transcription. HMGCS1 silencing abated the expression of ACSL4 in A431 cells. The level of ROS, lipid peroxidation, as well as iron accumulation were increased by itraconazole. Moreover, treatment with itraconazole impeded tumor growth in A431-bearing mice. Conclusion We proved itraconazole inhibits the growth of cSCC by regulating HMGCS1/ACSL4 axis.